Numerical study on heat transfer enhancement in a curved channel with baffles - Al-Juhais, Lafta Flayih Muhsin; Mas, Fawzi; Mohammad, Hafidh Hassan (Penerbit Akademia Baru, 2020)
Curved channel is commonly used in cement mill's journal bearing. In this study, heat transfer enhancement of curved channel having a rectangular cross-section with using inclined shape baffles is numerically investigated. The effects of different parameters of baffles, i.e. attack angle (α= 45°, 60°, and 90°), and the number of baffles (NB=9 and 13 baffles) are examined. The water is selected as working fluid for laminar and turbulent flow region. A standard k-ε turbulence model together with enhanced wall treatment is applied to solve the complex flow in Re of 500–5000. Influences of those parameters on heat transfer and friction performances in terms of Nusselt number, friction factor , Nussellt number enhancement ratio, and thermal performance factor, respectively are studied. The results show that the best condition to achieve maximum heat transfer at angle α = 90° , NB=13 and Re=5000 compared with other conditions. Furthermore, the maximum thermal performance factor (TEF) of the curved channel with using baffles is 4.4 at the same condition. This indicated that the geometry of baffles inside curved channel can improve the heat transfer significantly with reasonable increase in friction losses.